EFFECT OF POTASSIUM AND FOLIAR NUTRITION OF SECONDARY (Mg) AND MICRONUTRIENTS (Zn & B) ON YIELD ATTRIBUTES AND YIELD OF Bt - COTTON - and HARISH KUMAR SHARMA, D. SWETHA, P. LAXMINARAYANA, G. E. CH. VIDYASAGAR, S. NARENDER REDDY (The Journal of Research, PJTSAU, 2021)
A field experiment was conducted during kharif, 2015-16 and 2016-17 in split plot design to access the performance of Bt- cotton hybrid (MRC 7201 BGII) at Hyderabad with potassium fertilization (K @ 0, K @ 60 and K @ 90 kg ha-1) as main treatments and secondary (Magnesium) and micro nutrients (Zinc and Boron) as sub plot treatments. Among the potassium levels during both the years 2015 and 2016, K @ 90 kg ha-1 recorded significantly more number of bolls plant-1 (34.4, 36.4), boll weight (2.4, 2.5 g), seed cotton yield (1941, 2591 kg ha-1), stalk yield (1967, 2755 kg ha-1) and harvest index (58.1, 47.4 %) respectively in comparison to K @ 0 and K @ 60. Among the secondary (Magnesium) and micro nutrients (Zinc and Boron), during 2015 and 2016, treatment Mg1%Zn0.5%B0.1% showed more number of bolls plant-1 (33.0, 36.2), boll weight (2.43, 2.80 g), seed cotton yield (1512, 2324 kg ha-1), stalk yield (1622, 2708 kg ha-1) and harvest index (52.5, 44.1 %) when compared with all other treatments.